The Investigated Study of the COVID-19 Pandemic's Affect on Micro-Enterprises in Yogyakarta Province, Indonesia - Fridayani, Helen Dian; Chiang, Li-Chun (Universitas Pancasakti Tegal, 2023)
This research shall contribute to the growth of appropriate support frameworks for micro-entrepreneurs to thrive during and after a crisis through associated entrepreneurial development organizations. The coronavirus (COVID-19) pandemic has undeniably had an impact on the world economy and surroundings. Micro-enterprises, particularly in developing countries, have been hit hard by the COVID-19 outbreak. This paper employs personal insight and investigates the emergency situations management strategy throughout most of the pandemic COVID-19 outbreaks from the standpoint of micro-entrepreneurs. It is critical to investigate how micro-entrepreneurs deal with crises and what decisions they make to ensure the survival of their businesses. The results of participant observation shed light on microenterprises' business survival strategy and recovery plan during and after a crisis. According to the findings of this study, the impact of the COVID-19 pandemic was felt the most in Gunung Kidul and Kulon Progo in the Province of Yogyakarta. Aside from being remote from the city center, access to technology is also limited. In contrast to the more advanced cities of Yogyakarta, Bantul, and Sleman. Our research has suggested that micro-enterprise owners and other stakeholders reconsider their business strategies, including crisis scenarios and business continuity plans to virtually sustain customers in order to improve long-term development. We also suggest additional research areas to improve the successful digital transformation of micro-enterprises following the COVID-19 pandemic.